2016
DOI: 10.1128/aac.00035-16
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Substitution Pattern of 5-Aryl-2-Aminoimidazoles Allows Fine-Tuning of Their Antibiofilm Activity Spectrum and Toxicity

Abstract: We previously synthesized several series of compounds, based on the 5-aryl-2-aminoimidazole scaffold, that showed activity preventing the formation of Salmonella enterica serovar Typhimurium and Pseudomonas aeruginosa biofilms. Here, we further studied the activity spectrum of a number of the most active N1- and 2N-substituted 5-aryl-2-aminoimidazoles against a broad panel of biofilms formed by monospecies and mixed species of bacteria and fungi. An N1-substituted compound showed very strong activity against t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 94 publications
1
21
0
Order By: Relevance
“…For example, an inhibitor might be given prophylactically to inhibit Salmonella colonization in the gut when the risk of exposure to Salmonella is high, as is currently done with probiotics 72 and vaccines 73 . The potential for clinical application is further supported by our recent reports showing that 2-aminoimidazoles can inhibit biofilm formation in vivo in a subcutaneous model in rats 14 , have low cytotoxicity against different mammalian cell types (tumor cell lines and bone cells 35,74 ) and do not affect the survival of Caenorhabditis elegans, a small nematode that is widely used for toxicity testing and is considered to have high predictive value for toxicity in mammals 75 . However, while clinical potential clearly exists, the assays we report here are most reflective of industrial treatments.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…For example, an inhibitor might be given prophylactically to inhibit Salmonella colonization in the gut when the risk of exposure to Salmonella is high, as is currently done with probiotics 72 and vaccines 73 . The potential for clinical application is further supported by our recent reports showing that 2-aminoimidazoles can inhibit biofilm formation in vivo in a subcutaneous model in rats 14 , have low cytotoxicity against different mammalian cell types (tumor cell lines and bone cells 35,74 ) and do not affect the survival of Caenorhabditis elegans, a small nematode that is widely used for toxicity testing and is considered to have high predictive value for toxicity in mammals 75 . However, while clinical potential clearly exists, the assays we report here are most reflective of industrial treatments.…”
Section: Resultsmentioning
confidence: 85%
“…We next sought to put our anti-biofilm strategy where resistance is counter selected into action. 2-cyclopentenyl-5-(4-chlorophenyl)-2-aminoimidazole, a specific member of the class of 5-aryl-2aminoimidazoles was chosen as EPS inhibitor 34,35 (see below). We have previously reported that 5-aryl-2-aminoimidazoles prevent EPS production of S. Typhimurium by reducing the transcription of csgD and its regulon 36 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Novel synthetic molecules are under exploration. The activity spectrum of the most active N1and 2N-substituted 5-aryl-2-aminoimidazoles against single-and mixed-biofilms of Gram-positive and Gram-negative bacteria and C. albicans was assessed by Peeters et al [165]. Molecules with substituents at both the N1 and 2N positions had high activity against mixed Gram-positive and yeast biofilms (monospecies and mixed), excluding biofilms formed by Gram-negative bacteria.…”
Section: Innovative Treatments Of Other Diseasesmentioning
confidence: 99%